On the measurement of the barrel bore based on laser scanning and eccentricity correction - Jin, Wei; Zhang, Pengjun; Zhang, Xinyi; Shi, Zhiyu (Frontiers in Physics, 2025)
Measuring the bore of artillery barrels is often a challenging task due to limited automation, inaccuracies in measurement, and the need to process large volumes of test data. To tackle these issues, research has focused on utilizing high-precision laser technology for scanning and detecting barrel bores. This process involves creating a three-dimensional (3D) reconstruction of the bore morphology based on the collected test data. This work addresses the problem of eccentricity error during detection by developing a rotational model of the robot within the bore. The model aids in analyzing errors and introduces a position calibration method that utilizes a double Position Sensitive Detector (PSD). The bore of the barrel has been reconstructed using the Delaunay triangular section interpolation algorithm, resulting in a 3D contour structure of the artillery barrel bore. Experimental results demonstrate that the profile curve of the artillery barrel bore exhibits significant fluctuations before calibration, but becomes much more stable afterward. The maximum degree of calibration achieved was up to 40%. The 3D reconstructed model displays robust structural integrity and offers compelling visual corroboration for the test data. Furthermore, the recti-linearity of the corrected 3D model of the artillery barrel has been significantly improved in this work.